Assessment of Types, Factors Contributing to Violence Against Women and its Effects on the Health Seeking Behaviour of Women in Rubanda Town Council Rubanda District. - Byumvuhore, Stephen (Kabale University, 2024)
Violence against women (VAW) is a global and highly complex phenomenon affecting women‟s health-seeking behaviour differently in various contextual settings depending on its prevalence, type, and predisposing factors. This study assessed the prevalence of VAW, factors that predispose women to VAW, and the effect of violence on women‟s health-seeking behaviour in Rubanda Town Council, Rubanda District. A cross-sectional study collecting qualitative and quantitative data was conducted from 422 study participants, including 407 women, 4 probation officers, 6 police, and 10 Local council chairpersons. Frequencies, percentages, and logistic regression were used to achieve the objectives. Thematic analysis was used to analyze the qualitative data. Results indicated that of the 407 respondents, the majority were aged 23-27 years (81.8%), had primary education (56.3%), were Christians (95.8%), were married (83.3%), self-employed (74.9%) and Bakiga (76.7%). VAW stood at 52.3% and verbal VAW (70.0%) was the most prevalent. Factors that predisposed women to higher VAW were being married (AOR =3.3, 95%CI: 1.2-9.2p = 0.020) but worse when separated (AOR = 46.3, 95%CI: 4.0-533.4, p = 0.002). Alcoholism was protective against VAW with a lower likelihood of VAW, especially if both partners were involved in alcoholism compared to no alcoholism to any of them (AOR = 0.2, 95%CI: 0.1-0.5, p = 0.001). Only women having peers were associated with a high likelihood of VAW (AOR = 2.9, 95%CI: 1.0-8.0 p = 0.043). Inability to meet expectations of men compared to no expectations at all was associated with a lower likelihood of VAW (AOR =0.3, 95%CI: 0.1-0.9, p = 0.004) but higher when expectations of both men and women are not met (AOR = 1.1, 95%CI: 0.4-2.7, p = 0.891). Of the 407 respondents, VAW adversely affected most of the health-seeking behaviour, particularly attending ANC alone without husbands (84.5%) and delay to seek health care due to disagreements with the husband (82.6%). Measures in place to curb VAW included the majority reported seeking health care outside the home area (54.8%) although over half found it hard to share VAW experiences (62.9%) and forgot to visit health facilities for help (68.6%). VAW was generally high in Rubanda district, mostly reporting physical and emotional VAW with being not being married (single), alcoholism, and expectations not met protective against VAW yet VAW adversely affected ANC without husbands and delay to seek health care due to disagreements from the husband with minimal measures to curb VAW as victims preferred seeking health care outside home area of residence, hard to share VAW experiences and forgot to visit health facility for help. It is recommended that stakeholders should engage women through women/men groups and other associations should emphasize policies against women and report perpetrators to authorities.